Patient autonomy in the context of digital health - Soria, Salvador Tarodo (Bioethics, 2025)
Digital health opens the door to a promising horizon where the combination of several sciences and the application of new technologies can improve health, hope and quality of life. However, it is essential to ensure that such advances are compatible with and respectful of the right to privacy, data protection, right to information and freedom of choice, in short, with the autonomy of the human being in healthcare. The application of new technologies in healthcare settings generates considerably major ethical and legal challenges. This paper identifies some of the problems that could be more relevant, that is, the patient's consent in digital health, assessment of patient's capacity, how the implementation of new technologies changes the concept of medical intervention, the arrival of virtual identity or the legal responsibility of the parties acting herein. These are some of the questions that must be painstakingly analysed and correctly resolved to ensure that scientific and technological advances respect fundamentals rights in this new paradigm of digital health.